Effects of fluctuation oil price towards consumer / Siti Aishah Mohd Nordin - Mohd Nordin, Siti Aishah (2011)
Purpose – Fluctuations of oil price and petroleum products have had different effects on great economic variables. The aim of this paper is to investigate the effect of oil price fluctuation on the consumer’s income level, cost of goods and services and consumer inflation in Malaysia. Design/methodology/approach – The effects of oil volatility and fluctuation give good and bad impacts to consumer. Use exploratory design in order to answer all why and what questions for this study. All data had been run into SPSS software and data was used during the period 1990-2009. Besides that, oil price from Ron97 are used as a sample because it ore fluctuate and depends on global market price. Findings – While research results support previous studies about the relationship between the consumer’s income levels, cost of goods and services and consumer inflation. There are significant relationship between consumer’s income level, cost of goods and services and oil price. Therefore, the relationship between consumer inflation and oil price is insignificant. Research limitations/implications – The paper has considered oil price fluctuation on all industries in Malaysia. There a have complication during getting all the data because there are low accuracy of the figure. Besides that, this study will give good implications to other researcher as a reference. Originality/value – So far, several studies have been conducted in different countries regarding the subject of the study.